PROSEDUR PENANGANAN RESERVASI PAKET WISATA PT. PANORAMA TOUR AND TRAVEL DENPASAR - Melani Rosalina Hutabarat, Maria; Sasrawan Mananda, I GPB; Leli Kusuma Dewi, Luh Gede (Jurnal IPTA (Industri Perjalanan Wisata), 2017)
The travel agent plays an important to roles give all information about tourism destination to the world. Travel agents related activities which are conducted such as inbound and outbound tour, travel documents (passport/visa), ticketing, and the problem are how to handle reservation and find out about the solutions related. Quality and quantity data resources were using as primary and secondary data. Interview and documentation were using for data analysis with descriptive analysis technic. The procedure on how to handle package tour reservation such as: receive make a reservation of overseas agents, file the data and solution for fully booked hotel request, changes the reservations and client’s complaint. Based on the reseach, the company should improve the ability of the staff for correspondence with computerized system and more staff at the airport.
Keywords: Procedure, Reservation, Package Tour